Multiple Shooting in Rational Expectations Models - Lipton, David; Poterba, James; Sachs, Jeffrey; Summers, Lawrence (Econometrica, 1982)
Tht" note desc:,.-tb.. 8 n "I!:ort h,.for t hl!-lIolut lon of ratlom.\